2014
DOI: 10.1002/lary.25079
|View full text |Cite
|
Sign up to set email alerts
|

Audiologic presentation of enlargement of the vestibular aqueduct according to the SLC26A4 genotypes

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The reported percentage of biallelic SLC26A4 mutations in EVA cohorts range from 8% to 84%, suggesting a multifactorial diversity within each ethnic population. It probably also reflects different strategies of ascertaining patients and the use of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The reported percentage of biallelic SLC26A4 mutations in EVA cohorts range from 8% to 84%, suggesting a multifactorial diversity within each ethnic population. It probably also reflects different strategies of ascertaining patients and the use of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…In general, genes and variants with autosomal recessive inheritance cause congenital or early onset (prelingual) deafness, whereas genes with autosomal dominant inheritance lead to progressive hearing loss often with delayed onset. However, about one-half of patients with bilateral and about 10 % with unilateral EVA harbor biallelic SLC26A4 mutations associated with autosomal recessive nonsyndromic deafness or Pendred syndrome (14,15). These patients may suffer from sudden hearing loss even after minor head trauma (16).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the authors did not identify any phenotypic differences among patients with different SLC26A4 variants [26,34]. However, it has been recently reported that some variants might lead to progression of hearing loss [35,36], and some SLC26A4 genotypes might be associated with a normal thyroid phenotype and less severe hearing loss [37].…”
Section: Discussionmentioning
confidence: 96%